Transport in metal-oxide-semiconductor structures mobile ions effects on the oxide properties - Bentarzi, Hamid (Engineering materials, 2011)
This book focuses on the importance of mobile ions presented in oxide structures, what significantly affects the metal-oxide-semiconductor (MOS) properties. The reading starts with the definition of the MOS structure, its various aspects and different types of charges presented in their structure. A review on ionic transport mechanisms and techniques for measuring the mobile ions concentration in the oxides is given, special attention being attempted to the Charge Pumping (CP) technique associated with the Bias Thermal Stress (BTS) method. Theoretical approaches to determine the density of mobile ions as well as their distribution along the oxide thickness are also discussed. The content varies from general to very specific examples, helping the reader to learn more about transport in MOS structures.